2014
DOI: 10.1088/0004-637x/796/2/123
|View full text |Cite
|
Sign up to set email alerts
|

Dense Molecular Clumps Associated With the Large Magellanic Cloud Supergiant Shells LMC 4 and LMC 5

Abstract: We investigate the effects of Supergiant Shells (SGSs) and their interaction on dense molecular clumps by observing the Large Magellanic Cloud (LMC) star forming regions N48 and N49, which are located between two SGSs, LMC 4 and LMC 5. 12 CO (J=3-2, 1-0) and 13 CO(J=1-0) observations with the ASTE and Mopra telescopes have been carried out towards these regions. A clumpy distribution of dense molecular clumps is revealed with 7 pc spatial resolution. Large velocity gradient analysis shows that the molecular hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 77 publications
4
19
0
Order By: Relevance
“…For example, Fujii et al (2014) find dense molecular clumps at early stages of star formation between the LMC 4 and LMC 5 supershells. The expansion speeds of these superbubbles, which are 21 and 36 km/sec, respectively (Kim et al 1999), are similar to what we get in our simulations, but their observed sizes are much larger (i.e., radii of about 290 and 550 pc, assuming a distance of 50 kpc to the LMC).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, Fujii et al (2014) find dense molecular clumps at early stages of star formation between the LMC 4 and LMC 5 supershells. The expansion speeds of these superbubbles, which are 21 and 36 km/sec, respectively (Kim et al 1999), are similar to what we get in our simulations, but their observed sizes are much larger (i.e., radii of about 290 and 550 pc, assuming a distance of 50 kpc to the LMC).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Multitransition observations of molecular clouds in the LMC Heikkilä et al 1999;Israel et al 2003;Kim et al 2004;Bolatto et al 2005;Pineda et al 2008;Mizuno et al 2010;Minamidani et al 2008Minamidani et al , 2011Fujii et al 2014;Paron et al 2016) suggest that the molecular gas traced by CO may be warmer and/or denser than in our Galaxy. NH 3 (1,1) and (2,2) lines have been surveyed toward seven star-forming regions in the LMC by Ott et al (2010) using the Australia Telescope Compact Array (ATCA).…”
Section: Introductionmentioning
confidence: 92%
“…The kinetic temperatures of molecular clumps in the LMC have been calculated by multi-transition data of CO Heikkilä et al 1999;Israel et al 2003;Kim et al 2004;Bolatto et al 2005;Pineda et al 2008;Mizuno et al 2010;Minamidani et al 2008Minamidani et al , 2011Fujii et al 2014;Paron et al 2016). These observations show that the higher temperatures (T kin 100 K) occur in cloud regions that are of lower density ( 10 3 cm −3 ) and that the gas is colder (T kin = 10 -80 K) in regions of higher density (10 4 -10 5 cm −3 ).…”
Section: Comparison Of Temperatures Derived From H 2 Co Co Nh 3 Amentioning
confidence: 99%
“…The mass can be also estimated from the dynamical information of the size of the clumps and the linewidth of CO lines by assuming the virial equilibrium. We derived the virial masses from the 13 CO (J = 1-0) line using the procedure described by Fujii et al (2014) as follows. The virial mass is estimated as…”
Section: Virial Massmentioning
confidence: 99%